Mubi-Toram lexicon and Afro-Asiatic III: Lexemes with initial *ḅ- - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper is another part of a planned longer series designed to step by step reveal the Chadic and wider Afro-Asiatic cognate heritage in the lexical stock of the Mubi-Toram languages which represent the easternmost (27th) group of the vast (6th) Chadic branch of the gigantic Afro-Asiatic family.